Prevalence of foot ulcers in diabetic patients in Punjab, Pakistan - Akhtar, Sohail; Latif, Mujahid; Ahmed, Omer Shabbir; Sarwar, Aqsa; Alina, Ayisham; Khan, Muhammad Imran (Frontiers in Public Health, 2022)
Diabetes-related foot ulceration is prevalent and disabling, usually resulting in the amputation of the limb. The mortality rate is significant, and healed ulcers frequently reoccur. The main purpose of this study was to explore the prevalence of foot ulcers and their associated factors among diabetic patients in Punjab, Pakistan. Multistage cluster random sampling procedure was applied to perform a cross-sectional analysis in the state of Punjab, Pakistan. A sample of 1503 people with diabetes, including 504 men and 999 women, were selected from different hospitals. Data were collected from December 18, 2018, to June 30, 2019. Individuals of 18 years or above were selected. A binary multiple logistic regression analysis was utilized to find the factors associated with a diabetic foot ulcer. The overall prevalence of diabetic foot ulcers was 16.83% (95% CI: 14.9%–18.7%). The prevalence among the female was 17.52% (95% CI: 15.2%–19.9%), and the male was 15.48% (95% CI: 12.3%–18.6%). In rural areas, prevalence was 13.91% (95% CI: 10.6%–17.2%) compared to the prevalence of 17.96% (95% CI: 15.7%–20.2%) in the urban area. Individuals 75 years and above had the highest prevalence of 66.67% (95% CI: 51.9%–81.5%). According to the income status, subjects with monthly income above Rs. 61,000 had a prevalence of 24.24% (95% CI: 15.8%–32.7%), and among overweight subjects was 25.49% (95% CI: 21.3%–29.7%). This study found a relatively high prevalence of foot ulcers in Punjab, Pakistan. The results indicate that diabetic foot ulcers have become a major health problem in diabetic patients, and better strategies and preventive measures should be opted to deal with the epidemic.